Preparation of Cu2O Films with Preferred Crystal Orientations by Electrodeposition Method - Xu, Ling; Liu, Chang-Ling; Wu, Shi-Biao; Tao, Fang-Tao; Wu, Shi-Long (Asian Journal of Chemistry, 2014)
Cuprous oxide (Cu2O) films were electrodeposited by potentiostatic method on the indium tin oxide conductive glass substrate. The films were characterized by XRD and SEM. The electrodeposition process conditions for the preparation of Cu2O films with preferred orientations of (111) or (200) lattice plane were investigated. According to the result of experiments, the preferred crystal orientations of the obtained Cu2O films were related to electrodeposition potential and the molar ratio of CuSO4 vs. lactic acid in plating solution.